Obstetric and newborn outcomes and risk factors for low birth weight and preterm delivery among HIV-infected pregnant women at the University College Hospital Ibadan (2015)
There remains uncertainty about the impact of HIV on pregnancy outcomes and effects of highly active antiretroviral therapy on fetal development. This study describes obstetric outcomes among HIV positive parturients at the University College Hospital, Ibadan. HTV positive parturients were identified in the birth register. During the 30-month period, 318 of 6203 deliveries were HIV positive (5.1%) with 97.6% record retrieval. The mean age of the HTV positive parturients was 31.66 years (± 4.66); the mean gestational age at delivery was 38.02 weeks (± 2.75) and the mean birth weight 2.85kg (±0.59). There were 35.8% (109) preterm births, 2.9% stillbirths and 21.5% low birth weights. The regimen most commonly (198, 64.5%) used was a non-nucleoside reverse transcriptase (NNRTI) based HAART. Preterm births were similar following spontaneous vaginal delivery (31.5%) and elective section (31%) but higher (41.3%) with emergency section (p=0.4). On univariate analysis, the preterm infants had lower mean birth weights (2.46±0.61 vs 2.96±0.44; p=0.000). The proportion of preterm births was higher among Low birth weight infants (71.9% vs 28.1%; p=0.00). Variables with more preterm births were age >35 years (51.6%), ≤ 6years of schooling (51.5% vs 48.4%) and being on combination ARV (PI, 37.5% or non-PI, 36.2%). However, these differences did not attain statistical significance. Low birth weight infants had mothers who had higher mean ages (33.28 years ±4.59 vs 31.28 years ± 4.59,. p= 0.02), lower mean gestational age at delivery (35.72 weeks ± 3.16 vs 38.49 weeks ±2.1, p= 0.00). Variables with more low birth weight include <12years of schooling and being on mono/ dual therapy (31.8%). These differences were not statistically significant. On logistic regression, factors that retained an association with low birth weight were mean maternal age at delivery (p= 0.002; β- 0.904; 95% CI, 0.848 - 0.966) and being on mono/ dual therapy (p= 0.039; β= 3.042; 95% CI, 1.055 - 8.768). The only factor that retained an association with preterm birth was mean maternal age at delivery (p= 0.015; β= 0.935; 95% CI, 0.886-0.987). HIV positive (especially older) women, have high rates of preterm deliveries and low birth weights. The beneficial effects of HAART on mother-to-child transmission are indisputable but monitoring antiretroviral therapy in pregnancy remains a priority and antenatal surveillance should include fetal growth assessment.